The mediating roles of personal mastery and health-promoting behaviors in the relationship between self-regulatory fatigue and quality of life among patients with type 2 diabetes mellitus - Guiqiu Fang; Weidong Gong; Lihua Xia; Liping Li; Peng Sun; Jie Song; Yufeng Cui; Xiaochun Tang; Youxing Wu; Panfeng Li; Xiaoyan Zhang; Xing Ni; et al. (PLoS ONE, 2026)
Background Quality of life (QoL) is a pivotal prognostic indicator for patients with Type 2 Diabetes Mellitus (T2DM). While the impact of various factors on QoL is recognized, the complex interplay between psychological and behavioral determinants remains underexplored. Understanding these pathways is essential for developing effective interventions. Objective This study aimed to investigate the status of QoL and its associated factors among T2DM patients, and to examine the mediating effects of personal mastery (PM) and health-promoting behaviors (HPB) in the relationship between self-regulatory fatigue (SRF) and QoL by using structural equation modeling. Methods The study adhered to the STROBE guidelines for cross-sectional reporting. From July 2025 to February 2026, 432 T2DM patients were recruited from three tertiary grade-A hospitals across two cities in China by using convenience sampling. Data were collected using the Demographic Characteristics Questionnaire, Self-Regulatory Fatigue Scale, Personal Mastery Scale, Diabetes Health Promotion Scale, and Diabetes-Specific Quality of Life Scale. Pearson’s correlation, multiple linear regression, and structural equation modeling were employed for data analysis. The mediating effects were tested using the bias-corrected (BC) bootstrap method with 5,000 resamples. Results The total scores for SRF, PM, HPB, and QoL were 38.63 ± 12.84, 26.12 ± 7.62, 97.69 ± 20.87, and 69.41 ± 20.89, respectively. Correlation analysis indicated that QoL was significantly positively correlated with SRF ( r = 0.581, p < 0.01), and negatively correlated with PM ( r = −0.557, p < 0.01) and HPB ( r = −0.613, p < 0.01). Multiple linear regression analysis revealed that age, educational level, medical insurance payment method, smoking status, glycemic control status, number of comorbidities, self-care ability, self-regulatory fatigue, personal mastery, and health-promoting behaviors were independent predictors of QoL. Furthermore, the structural equation modeling demonstrated a significant total indirect effect of self-regulatory fatigue on QoL. The mediating effect of personal mastery accounted for 30.2% of the total indirect effect, while that of health-promoting behaviors explained 60.2%. The chain mediating pathway contributed 9.5% of the total indirect effect. Conclusion This study suggests that SRF is statistically associated with directly and indirectly poorer QoL in T2DM patients, primarily by being associated with lower PM and fewer HPB. These findings highlight the importance of addressing psychological and behavioral mechanisms in diabetes care. From a nursing perspective, interventions targeting SRF, strengthening PM, and promoting HPB may be beneficial.